2013
DOI: 10.1016/j.ygyno.2012.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression signatures differentiate uterine endometrial stromal sarcoma from leiomyosarcoma

Abstract: Objective Endometrial stromal sarcoma (ESS) and leiomyosarcoma (LMS) are the two most common uterine sarcomas, but both are rare tumors. The aim of the present study was to compare the global gene expression patterns of ESS and LMS. Methods Gene expression profiles of 7 ESS and 13 LMS were analyzed using the HumanRef-8 BeadChip from Illumina. Differentially expressed candidate genes were validated using quantitative real-time PCR and immunohistochemistry. Results Unsupervised hierarchical clustering using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 61 publications
1
31
0
1
Order By: Relevance
“…Genetic profiling is investigational in LMS, but could potentially elucidate treatment targets. 16,17 Genetic profiling may be able to improve prognostication by identifying gene signatures that differentiate indolent uterine LMS tumors from clinically aggressive tumors (J. Barlin and D. Levine, personal communication, July 2014).…”
Section: Molecular Biology and Geneticsmentioning
confidence: 99%
“…Genetic profiling is investigational in LMS, but could potentially elucidate treatment targets. 16,17 Genetic profiling may be able to improve prognostication by identifying gene signatures that differentiate indolent uterine LMS tumors from clinically aggressive tumors (J. Barlin and D. Levine, personal communication, July 2014).…”
Section: Molecular Biology and Geneticsmentioning
confidence: 99%
“…New immunomarkers are thus needed to face this challenging problem 21. Novel gene expression signatures differentiating ESS from ULMS, conducted by Davidson et al ,22 have recently emerged. The authors found that genes that were overexpressed in ESS were: SLCA7A10/ASC1 , EFNB3, CCND2, ECEL1, ITM2A, NPW, PLAG1 and GCGR.…”
Section: Introductionmentioning
confidence: 99%
“…Genes that were overexpressed in ULMS were : CDKN2A, FABP3 , TAGLN, JPH2, GEM, NAV2 and RAB23. 22 Of all of these proteins, transgelin (TAGLN) was the only antibody shown in a small number of uterine sarcomas and soft tissue sarcomas to have promising results 23 24…”
Section: Introductionmentioning
confidence: 99%
“…On the other side, CD10 was not overexpressed in endometrial stromal sarcoma. This is even used as a marker of endometrial neoplasms [61].…”
Section: Mesenchymal Tumorsmentioning
confidence: 99%
“…Davidson et al [61] discovered further genes overexpressed in primary uterine leiomyosarcomas including OSTN, NLGN4X, NLGN1, SLITRK4, MASP1, XRN2, ASS1, RORB, HRASLS, and TSPAN7. They also found out different genes overexpressed in metastases of leiomyosarcomas including TNNT1, FOLR3, TDO2, CRYM, GJA1, TSPAN10, THBS1, SGK1, SHMT1, EGR2, and AGT.…”
Section: Mesenchymal Tumorsmentioning
confidence: 99%